Development Of Artıstıc And Aesthetıc Competence Of Future Teachers - Rabbimova F.T, Mavlonova S.Kh, Makhammadiev D.M, Ikromov D.N Ravshanov Sh.I (International Journal of Advanced Science and Technology, 2020)
The resultative criterion of the model for improving the artistic-aesthetic competence has been improved based on the optimization of educational (enriching the knowledge on artistic-aesthetic activities), normative (raising the axiological consciousness of students on environmental protection) and practical (environmental protection by students, researching) activities;